KEEFEKTIFAN STRATEGI PEMBELAJARAN CROSSWORD PUZZEL TERHADAP HASIL BELAJAR SISWA KELAS V DI SDN WONOTINGAL KOTA SEMARANG - Yunik Ekawati; M. Prayito; Bernardus Irianto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The crossword puzzle learning strategy is an active learning strategy for students that can be used as a good learning tool without losing the essence of ongoing learning. In fact, this strategy actively involves students from the start. Through crossword puzzles or crossword puzzles learn something complicated and think about how to solve crossword puzzles correctly. The crossword puzzle strategy is very good to use in the learning process because it can stimulate students to play an active role in the learning process. By using the crossword puzzle learning strategy, it is hoped that it will have a good impact on student learning outcomes. This research aims to determine the effectiveness of the Crossword Puzzle learning strategy on the learning outcomes of class V D students at SDN Wonotingal, Semarang City. The research method used is quantitative with a One Group Pretest-Posttest Design. Data was collected through pretest and posttest and analyzed using statistical methods. The research results show an increase in student learning outcomes after implementing the Crossword Puzzle learning strategy. The average pretest score was 45.19 and the average posttest score was 77.04. The results of the N-gain test are categorized as quite effective with the medium category getting an N-gain score of 0.6200 and an N-gain percent with a score of 61,9988. The significance value (2-tailed) has an average of -31.852 and 0.001. It can be concluded that there is a comparison between the results of the pretest and posttest if the significance figure is less than 0.05, which means Ho is rejected and Ha is obtained. The results proved that there was an influence on student learning outcomes before learning using the Crossword Puzzle learning strategy was implemented and after it was implemented.